Gold nanoparticles: From nanomedicine to nanosensing - Po C Chen (Dove Medical Press, 2008)
Po C Chen, Sandra C Mwakwari, Adegboyega K OyelereSchool of Chemistry and Biochemistry, Parker H Petit Institute for Bioengineering and Bioscience, Atlanta, GA, USAAbstract: Because of their photo-optical distinctiveness and biocompatibility, gold nanoparticles (AuNPs) have proven to be powerful tools in various nanomedicinal and nanomedical applications. In this review article, we discuss recent advances in the application of AuNPs in diagnostic imaging, biosensing and binary cancer therapeutic techniques. We also provide an eclectic collection of AuNPs delivery strategies, including assorted classes of delivery vehicles, which are showing great promise in specific targeting of AuNPs to diseased tissues. However, successful clinical implementations of the promised applications of AuNPs are still hampered by many barriers. In particular, more still needs to be done regarding our understanding of the pharmacokinetics and toxicological profiles of AuNPs and AuNPs-conjugates.Keywords: gold nanoparticles (AuNPs), targeted delivery, receptor-mediated endocytosis (RME), near infrared (NIR), surface plasmon resonance (SPR), surface-enhanced Raman scattering (SERS), bioimaging, biosensing, photothermal therapy